Minimally invasive surgical oncology state-of-the-art cancer management - Matteotti, R.; Ashley, Stanley W.; SpringerLink (Online service). (Berlin London Springer, 2011)
The past 20 years have witnessed an extraordinarily rapid adoption of minimally invasive surgical techniques, and increasingly these techniques are being employed in the diagnosis and treatment of a wide range of malignancies. This book is designed to serve as a unique and comprehensive overview of the current status of minimally invasive surgery in oncology patients and in addition offers valuable insights into the future of this constantly evolving field. The first section of the book is devoted to essential background information and to explaining what is physiologically distinctive in the cancer patient undergoing laparoscopic surgery. The second section then examines in detail a wide range of clinical aspects and issues across different disciplines, with clear instruction on the use of minimally invasive procedures. The aim is to enable the reader to make treatment decisions appropriate to the individual patient, to carry them out effectively, and to institute suitable postoperative care. Summaries of the latest knowledge in traditional therapies such as chemotherapy are also provided when appropriate. Each chapter is written by a recognized expert, and numerous high-quality illustrations are included to assist understanding. This book will serve both as a clinical reference guide and as an operative atlas, and is certain to prove invaluable in daily clinical practice.
Preface -- Foreword -- Part A - General Topics: Minimal Invasive Surgery - The Pioneers -- Evolution of Minimal Invasive Surgery and its Impact on Surgical Residency Training -- Laparoscopy and Research in Surgical Oncology: Current State-of- the-Art and Future Trends -- Moral and Ethical Issues in Laparoscopy and Advanced Surgical Technologies -- Robotic Application in Surgical Oncology -- Laparoscopy and Malignany-General Aspects -- Laparoscopy and Immunology -- Pneumoperitoneum and its Effects on Malignancy -- Laparoscopy in the Elderly -- Transluminal Surgery: Is there a Place for Oncological Procedures? - Part B Special Topics: Cancer of the Esophagus and the Gastro-Esophageal Junction: Two Cavity Approach -- Transhital Approach -- Cancer of the Stomach: Laparoscopic Distal Gastrectomy - LADG -- Laparoscopic Total Gastrectomy - LATG -- Endoluminal Procedures for Early Gastric Cancer -- Small Bowel: Cancer of the Small Bowel/Carcinoid.-- Cancer of the Colon and Rectum: Right Hemicolectomy and Appendix -- Left Hemicolectomy and Sigmoid Colon -- Surgery of the Rectum -- Cancer of the Hepato-Biliary System: General Considerations -- Liver - Non-anatomical Resection -- Liver - Anatomical Resection -- Cancer of the Gallbladder and Extrahepatic Bile Ducts -- Sleen: Sleen - Hematological Disorders -- Endocrinology: Cancer of the Thyroid -- Cancer of the Parathyroid -- Cancer of the Pancreas - Distal Resection and Staging of Pancreatic Cancer -- Cancer of the Pancreas - The Whipple Procedure -- Cancer of the Adrenal Gland -- Gynecology: Minimal Invasive Management of Gynecologic Malignancies -- Urology: Cancer of the Kidney -- Cancer of the Prostate -- Cancer of the Urinary Bladder -- Pediatrics: Minimal Invasive Management of Pediatric Malignancies -- Lung and Mediastinum: Minimal Invasive Management of Intra-Thoracic Malignanicies -- Index.
Electronic reproduction.
Keywords: Cancer -- Endoscopic surgery; Electronic books